Las mujeres en la pobreza - Alatorre, Javier (Book collections on Project MUSE., 1994)
"Collection of nine works explores relationships between social construction of gender, causes of poverty, and its intergenerational transmission. One section examines poor households, focusing on theoretical, conceptual, and methodological developments pertaining to inequality, poverty, and gender. Other sections discuss women's poverty in relation to urban and rural work, and mental and reproductive health. The final section addresses efforts of private and public sectors to counteract poverty"--Handbook of Latin American Studies, v. 57.